Sanad Pengajian Al-Quran: Suatu Perbincangan Awal - Muhammad Lukman Ibrahim; Mohd Azhar B. Abdullah (Fakulti Pengajian Quran dan Sunnah, 2025)
E-Proceeding The 9th International Conference on Nabawi Heritage (SWAN 2024) Theme: Prophetic Legacy in Development of Civil Society in the Era of Artificial Intelligence (AI) 6-7 November 2024